The Influence of Strategic Entrepreneurship and Individual Development on Competitive Advantage in Social Entrepreneurship Organizations (Case Study of TAULAN Community) - Nurkasih, Amelia; -, Jusni; Dewi Sugiharti Tikson, Shinta (UI Scholars Hub, 2023)
A social entrepreneurship organization is an organization running entrepreneurial activities primarily oriented to the welfare of the community and its social mission. As a business, social entrepreneurship needs to gain a competitive advantage in similar businesses and other businesses that are the main competitors. This can be achieved when social enterprises have human resources who are aware of opportunity-seeking behavior and profit-seeking behavior, which are the main dimensions of strategic entrepreneurship. In addition, in the face of changing business conditions, organizations need to provide space for their members to learn through individual development, both in terms of opportunities and facilities. This study aims to determine the effect of strategic entrepreneurship and individual development on competitive advantage in social entrepreneurship organizations. The population in this study comprises 35 individuals from the TAULAN Community, a social enterprise engaged in the creative industry and aiming to empower incarcerated juveniles and women. Saturated sampling was used to obtain the participants. Data was collected using a questionnaire. Multiple regression analysis was performed with IBM SPSS Version 28.1 software. The results of this study indicate that strategic entrepreneurship has no significant effect on TAULAN Community’s efforts to achieve competitive advantage, and individual development has a significant effect on competitive advantage in social entrepreneurship organizations.